935 nm-diode-pumped passively Q-switched Er:Yb:Sr3Gd2(BO3)4 pulse laser at 1.5–1.6 μm. (August 2021) - Chen, Yujin; Huang, Jianhua; Lin, Yanfu; Gong, Xinghong; Luo, Zundu; Huang, Yidong
Highlights: The Er:Yb:SGB crystal has a broad and flat absorption band around 940 nm. 1534 nm passively Q -switched laser was firstly realized in the Er:Yb:SGB crystal. The Er:Yb:SGB crystal is a good 1.5–1.6 μm laser medium pumped by a 940 nm LD. Abstract: Eye-safe 1.5–1.6 μm pulse laser passively Q -switched by a Co 2+ :MgAl2 O4 crystal was realized in a Z -cut, 1.8 mm-thick Er:Yb:Sr3 Gd2 (BO3 )4 crystal end-pumped by a 935 nm laser diode. A 1534 nm pulse laser with energy of 9.1 μJ, repetition frequency of 15.6 kHz, and duration of 29 ns was obtained at an absorbed pump power of 2.5 W. Polarization of the output laser beam was measured to be linear and parallel to the Y optical indicatrix axis. Benefited from a broad and flat absorption band between 920 and 950 nm, the Er:Yb:Sr3 Gd2 (BO3 )4 crystal may be a good gain medium for 1.5–1.6 μm laser pumped by a common commercial diode laser around 940 nm.